Perceptions of Academicians towards Instructional Practices of Music Education in Tribhuvan University - Pokharel, Ramesh (Journal of Fine Arts Campus, 2021)
Music is a subject through which one can express their feelings in an artistic way including melody and rhythm. The aim of the research was to study the perception of academicians towards the present context of the curriculum, teaching methods, and evaluation system of music education at Tribhuvan University (TU). The qualitative research design was employed in the research. 23 academicians from TU were purposively selected for data collection and data were analyzed by descriptive and word cloud methods. The finding indicates that the teaching methods, examination system, and methods of designing curriculum are traditional in music education on TU. Additionally, the participants of this research suggested that the stakeholders should be serious, sensitive, and careful to adopt modern instructional practices in music education-related programs. Furthermore, modern technologies and changing aspects of society should be incorporated into the curriculum and pedagogical practices. The finding of this research is applicable to improving the current policy and practices of music education programs on TU.